EVALUASI PROGRAM KARTU JAKARTA PINTAR (KJP) DI SMAN 22 JAKARTA TIMUR DENGAN PENDEKATAN CIPP - Chaerul Anwar (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2020)
To increase student learning opportunities up to high school level, the DKI Jakarta government provides the Jakarta Smart Card (KJP) program for people who are classified as poor. Evaluation on the implementation of this program needs to be done to see the extent of program success. This study aims to look at the evaluation of the KJP program at SMA Negeri 22 Jakarta using the CIPP (Context, Input, Process, Output) method. The results showed that SMAN 22 had run the KJP program very well. The results of the evaluation on context aspect shows a very good result with 85% of implementation. The input aspects have been carried out 80% with good categories. The process aspect is running well with a percentage of 80% of the plan, and the product evaluation (output) aspect also reaches 80% of the specified criteria. The study also recommends that there should be an officer from provincial government officials to conduct home visit program to maintain the quality of KJP implementation.